Updating Labor Legislation in the Context of Introducing Independent Forms of Work: Telecommuting and Work from Home - A. L. Klymenko (Law and Safety)
The preconditions and directions of improving legal regulation of telecommuting have been studied. The author has found out the specifics of the legal nature of the concepts of “work from home” and “telecommuting” in terms of the approach to the possibilities of various forms of labor organization and labor relations regarding the events related to the pandemic (COVID-19) and consequences for the Ukrainian labor market. Based on the application of general and special methods of scientific cognition, the author has clarified the essence and has expanded the content of two independent types (forms of work): telecommuting and work from home in the context of amendments in domestic labor legislation (draft Law No. 4051: Articles 601 and 602).